فاعلية تطبيقات الذكاء الاصطناعي في تحقيق جودة التدقيق الخارجي: دراسة ميدانية - زكريا كرثيو; مهاجر علاء الدين; عمر سعد الله (جامعة الوادي University of Eloued, 2025)
"تهدف هذه الدراسة إلى التعرف على فاعلية تطبيقات الذكاء الاصطناعي في تحقيق جودة التدقيق الخارجي، في ظل التحولات المتسارعة في بيئة العمل. وتم الاعتماد على المنهج الوصفي التحليلي، من خلال استبيان شمل عينة من المحاسبين ومحافظي الحسابات وخبراء محاسبيين وأساتذة في التخصص لدراسة العلاقة بين فاعلية تطبيقات الذكاء الاصطناعي وأبعاد جود التدقيق الخارجي (مصداقية التقارير المالية، الامتثال لمعايير المحاسبة والتدقيق المعتمدة، الشفافية وضمان دقة الفحص)، حيث كان حجم العينة 31 فردا. وتوصلت الدراسة إلى: -توجد فاعلية لتطبيقات الذكاء الاصطناعي في تعزيز مصداقية التقارير المالية -توجد فاعلية لتطبيقات الذكاء الاصطناعي في ضمان الامتثال لمعايير المحاسبة والتدقيق المعتمدة توجد فاعلية لتطبيقات الذكاء الاصطناعي في تعزيز الشفافية وضمان دقة الفحص "This study aims to identify the effectiveness of artificial intelligence applications in achieving the quality of external auditing, in light of the rapid transformations in the work environment. The descriptive analytical approach was adopted, using a questionnaire distributed to a sample of accountants, auditors, accounting experts, and specialized professors. The objective was to examine the relationship between the effectiveness of artificial intelligence applications and the dimensions of external audit quality, namely: the credibility of financial reports, compliance with established accounting and auditing standards, and transparency and accuracy of inspection. The sample size consisted of 31 participants. The study concluded that: Artificial intelligence applications are effective in enhancing the credibility of financial reports Artificial intelligence applications are effective in ensuring compliance with accounting and auditing standards Artificial intelligence applications are effective in promoting transparency and ensuring the accuracy of inspection
ماسترالعلوم المالية والمحاسبية
Keywords: تقنيات ذكاء اصطناعي; التدقيق الخارجي; جودة تدقيق خارجي; Artificial Intelligence Technologies; External Auditing; External Audit Quality